Smart Contracts in the New Era of Contract Law - Alexandros A. Papantoniou (Цифровое право, 2020)
This essay examines whether smart contract innovation is capable of displacing the orthodox adherence to traditional contracts. This examination is underpinned by an analysis of the legality of smart contracts, through which it is exemplified that smart contracts ought to be considered legally binding instruments. The essay proceeds to explore the superiority of smart contracting on a technical and theoretical basis. The advantages generated through smart contract automaticity and enforceability present a concrete basis for undermining reliance on traditional contracts. Blockchain Technology also enhances the benefits of smart contracts by acting as a smart contract enabler through guaranteed performance and enforceability. Nevertheless, such novel technologies inevitably suffer from several shortcomings. This essay considers examples which illustrate the inflexibility of smart contracting. Apart from being susceptible to hacking and code exploitation, smart contracting is unable to deal with ambiguities and potential modifications. Overall, this suggests that the advantages of smart contract practice are currently confined to some specified limited scenarios. Smart contracts perform a different function to traditional contracting by merely guaranteeing technical enforceability as opposed to legal enforceability. This essay thus concludes that, for the time being, it is best to regard smart contracting as a supplement to traditional contracts rather than an outright displacement.